The Effect of Remote Learning, Family Condition, and Mental Resilience on Depression Symptoms of Early Childhood - I Wayan Karta; Ni Wayan Rasmini; I Wayan Widiana; Putu Rahayu Ujianti (Emerging Science Journal, 2022)
The Covid-19 pandemic that attacked Indonesia and other countries of the world has changed human’ way of life. The Covid-19 pandemic greatly influences the field of education, where all learning activities turn to online mode, which results in students’ depression symptoms due to their unpreparedness. This study aims to analyze the impact of remote learning, family conditions, and mental resilience on depression symptoms in early childhood. This study used ex-post facto research (measurement after the event) because the research data for both independent variables and dependent variables occurred before this study was held. The study population was 80 children. The data collection method used was a questionnaire developed from the indicators of each variable. The analysis method used multiple regression. The data analysis used correlation and regression techniques, with regression analysis of three predictors and one criterion. The research findings showed that depression symptoms of early childhood are jointly influenced by remote learning, family condition, and mental resilience. However, two variables that do not affect the depression symptoms of early childhood are remote learning and mental resilience. It can be recommended that parents and parties involved in early childhood education give more attention to children. Doi: 10.28991/ESJ-2022-06-06-013 Full Text: PDF